The religious factor in regional identity policy: self-presentation of Chechen leaders in the social networks - Mikhaleva, A.V. (Perm Federal Research Centre Journal, 2020)
Contemporary network society with the exclusive role of Internet communications is significantly changing all spheres of life, opening up additional opportunities for manipulating public consciousness through virtual channels. The article looks into the religious aspect of self-presentation 0f several leaders 0f the Chechen Republic in the s0cial netw0rks and c0nsiders h0w the “religi0us factor” is actualized 0n the Internet pages 0f the p0litical and religi0us elite 0f the republic. The social political analysis of the views and attitudes of elite groups allows us to determine the development vectors of the regional community and to predict emerging problems, the main characteristics and elements of which are reflected on social network pages. The article presents the results of a sociological study of Internet activity of the Chechen elite on the VKontakte, Instagram and Telegram pages. The study was based on network analysis, that is, a noncontact method of digital sociology, taking into account the normative, visual and substantial aspects of the presentation of the studied objects. The following political and religious leaders of the Chechen Republic were chosen: Ramzan Kadyrov, the Head of the Chechen Republic, Muslim Khuchiev, the Chairman of the Chechen Government, Adam Shakhidov, the Advisor to the leader of the Chechen Republic on religious issues, and Salah Mezhiev, Mufti of the Chechen Republic. The analysis of their publication activity and textual content of comments was carried out, which allowed us to identify the key strategies for incorporating religious resource in the regional identity policy. As a result of the study, the high significance of the religious resource for the ideological substantiation of political actions of the regional elite was revealed. Moreover, the reference to the religious context is instrumentalistic and is determined by the political conjuncture. In conclusion, the most problematic points of religious discourse of the Chechen leaders are indicated.